Intestinal parasites in children from a day care centre in Matanzas City, Cuba. - Roberto Cañete; Mariuska Morales Díaz; Roxana Avalos García; Pedro Miguel Laúd Martinez; Félix Manuel Ponce (PLoS ONE, 2012)
BACKGROUND: Intestinal parasitic infections are widely distributed throughout the world and children are the most affected population. Day care centres are environments where children have proven to be more susceptible to acquiring IP. METHODS AND PRINCIPAL FINDINGS: A cross-sectional study was carried to determine the prevalence of intestinal parasites in stool samples among children who attend to a day care centre in an urban area of Matanzas city, Cuba, from March to June 2012. 104 children under five years old were included on the study after informed consent form was signed by parents or legal guardians. Three fresh faecal samples were collected from each child in different days and were examined by direct wet mount, formalin-ether, and Kato- Katz techniques. Data relating to demography, socioeconomic status, source of drinking water, and personal hygiene habits were also collected using a standardized questionnaire. In total, 71.1% of children harbored at least one type of intestinal parasite and 47 (45.2%) were infected by more than one species. Giardia duodenalis and Blastocystis sp. were the most common parasites found, with prevalence rates of 54.8% and 38.5% respectively. CONCLUSIONS: Despite public health campaigns, improvement in the level of education, and the availability of and access to medical services in Cuba infections by intestinal protozoan is high in this centre. Almost nothing is published regarding intestinal parasites in Matanzas province during the last 40 years so this work could also be the initial point to carry out other studies to clarify the IP status in this region.